THEORETICAL AND PRACTICAL ASPECTS OF THE FORMATION OF IT INDUSTRY HR-BRAND DEVELOPMENT STRATEGY - PENIUK, Valeriia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article is devoted to the study of theoretical and practical aspects of the development strategy of the HR brand in the IT industry. It is substantiated that the creation of an attractive HR brand is a guarantee of the effective development of the activities of many IT companies. It was determined that although HR-branding is a driver in the labor market, in the current conditions of Ukraine, the employer’s brand is insufficiently researched in scientific circles. It is determined what characterizes the need for the formation of an HR brand under the conditions, if the company has a development plan and future prospects, plans to enter new markets and open offices abroad, or seeks to maintain the efficiency and productivity of the existing team. It has been proven why the main objects of influence of the company’s internal HR brand are employees, and the external one - people who are looking for a job. The internal and external objects of the HR brand are characterized. The author’s interpretation of the HR brand of the IT industry is given, where it is determined that the HR brand from the position of the company-employer is a set of meaningful (what the organization offers to its current or potential employee) and communicative characteristics (the form in which it does this). HR brands were analyzed, in particular IT companies with positive dynamics in terms of the number of specialists and the best IT companies to work for. The list of criteria for choosing an employer in the IT industry is given, as well as the rating of the best IT companies according to the choice of IT specialists. It was determined that the HR brand strategy should include work on the internal brand and promotion of the external brand. The influence of the war on the work of companies and the relationship to the formation of the HR brand is substantiated, and it is explained why some enterprises entered new regions of their own free will or at the request of customers. The conclusion includes measures to preserve the positive image of the company and form an effective strategy for the development of the HR brand in the IT industry.